Histological and chemical view on parotid duct sialolithiasis in the Slovakian warmblood mare - Korim, Filip; Revajová, Viera; Koľvek, Filip; Bujňák, Lukáš; Hreus, Sebastián; Všianský, Dalibor (Veterinary research communications, 2024)
The parotid duct has been reported to be the most common site of sialoliths in horses. In this case report, we described the first confirmed case of the equine sialolithiasis in Slovakia. The work was aimed to describe the transcutaneous approach to removing the sialolith, which manifested as a hard painless mass in the area of the maxillary cheek teeth, in a 14-year-old Slovakian warmblood mare. Pathological-anatomical and histological examination after extirpation confirmed the presence of parotid duct ectasia resulting from calculus. The mineral composition of the sialolith was determined with atomic absorption spectroscopy using X-ray powder diffraction. The sialolith was successfully extirpated transcutaneously, without complications or recurrence.
Keywords: Animals; Salivary Duct Calculi; Salivary Gland Calculi; Female; ženské pohlaví; nemoci koní; Slovakia; Sialolith; Chemistry; koně; kaménky ve slinných žlázách; Horses; Histology; Parotid duct; Equine; Slovenská republika; zvířata; Parotid Gland; parotis; Horse Diseases; kaménky ve vývodu slinných žláz